THE ANALYSIS OF MOOD TYPES IN STEVE JOBS’ AND BARACK OBAMA’S SPEECHES - Slamet Utomo; Rusiana Rusiana; Putri Minarosa (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2018)
This research aims to find the differences and similarities of mood types and describe the interpretation of mood types used in the speeches of Steve Jobs as a businessman and Barack Obama as a politician. The design of the research is descriptive qualitative. The result of this research shows that both of the speeches have three types of mood, they are declarative, interrogative and imperative. From the data results, it can be concluded that there are a difference and two similarities of mood types found in the speeches and the interpretation of mood types used in the speeches. At the conclusion of the research, the researchers suggest for students of college and further researcher to analyze mood types in another sources, such as in form of poem or advertisement.